Effect of Bacillus firmus and other sporulating aerobic microorganisms on in vitro stimulation of human lymphocytes. A comparative study - Prokesová, L; Nováková, M; Julák, J; Mára, M (Folia microbiologica, 1994)
B. firmus activates human peripheral blood lymphocytes in vitro. Bacteria inactivated by heat or by formaldehyde were about equally effective, stimulating the blastic transformation of lymphocytes at doses of 10-200 mg/L and Ig formation in the culture at 10-500 mg/L. The action of formaldehyde treated B. firmus was compared with that of analogously inactivated B. subtilis, B. polymyxa, B. coagulans, B. megaterium, B. pumilus, B. cereus and B. lentus at a concentration of 100 mg/L. All these bacilli mildly stimulated blastic transformation and most of them substantially stimulated Ig formation, but B. firmus was the most efficient in stimulating the formation of Ig of all classes, in particular IgM and IgA. Its effect on Ig formation was comparable with that of PWM and was unusually high as compared with that of other bacteria. B. firmus is apparently a strong polyclonal activator of B lymphocytes. Its cells or their components could be potentially used for modulating immune reactions.
Keywords: Hot Temperature; mitogeny líčidla amerického; imunoglobulinové izotypy; vysoká teplota; aktivace lymfocytů; Pokeweed Mitogens; lymfocyty; Formaldehyde; Humans; Lymphocyte Activation; formaldehyd; Bacillus; Lymphocytes; lidé; Immunoglobulin Isotypes